Exploring the impact of "climate change" on lifetime replacement costs for long-span bridges prone to torsional flutter. Issue 140 (May 2015) - Seo, Dong-Woo; Caracoglia, Luca
Abstract: This study employs a computational framework for lifetime cost analysis of long-span bridges, induced by damage under high winds. Replacement costs due to structural collapse, caused by incipient torsional flutter instability, are examined. Information on the probability of mean wind speed at a given site and on the aeroelastic coefficients of bridge decks (flutter derivatives) is used to predict the expected value of the lifetime replacement costs due to flutter occurrence. This study explores the influence of "climate change" on the lifetime replacement costs, by suitable modification of the parameters describing the mean wind speed probability distribution and the occurrence of the high-wind events. Aeroleastic coefficients of a box-type bluff deck, reproduced from the results of the "United States-Japan Benchmark Study on Flutter Derivatives", are utilized in conjunction with literature experimental data of a truss-type deck to financially project the flutter-induced collapse probability on the long-term replacement costs of two simulated bridges.